Allergy to Beta-Lactams in Patients Consulting Allergology Center of the Antioquia University, Colombia (2014)
ABSTRACT: Rationale To determine the immunological component of patients who are test with suspected of adverse reaction to beta-lactams in clinical allergology center of Antioquia University in the period between January 2008 and October 2013. Methods Patient histories were obtained of electronic medical records, and they were offered investigation for penicillin allergy with specific IgE, skin prick tests, intradermal tests (IDT), patch test and drug challenge tests. Patients with case histories of reactions to other b -lactams were also subsequently challenged with the culprit drug. Results 590 allergy tests were made, 33 (15.6%) specific IgE by immunoCAP, 78 (36.9%) IDT, 13 (6.1%) patch test and 92 drug challenge tests. We studied 125 patients, 71 (56.8%) were females. 73 patients had an immediate reaction, and 52 a non-immediate reaction. The severity of the reported reactions was low in most cases: cutaneous rash and/or angioedema 95 (73.6%), anaphylaxis 10 (7.7%), lower respiratory symptoms 2 (1.5%), nonspecific symptoms 8 (6.2%). The drug most frequently involved was amoxicillin in 62 patients (49.6%), crystalline penicillin G 17 (13.6%), benzathine penicillin 15 (12%), cephalexin 13 (10.4%), Analysis of clinical histories showed that patients with a well-defined history of allergy and a history of anaphylaxis were more likely to have a positive test compared to patients with vague histories. Conclusions The data suggest that case history is often insufficient to discriminate between immediate reactors and non-immediate reactors. A minority of patients presenting with a history of b-lactam allergy have evidence of immune-mediated hypersensivity in this study.